BOOK REVIEW Leenders, T. 2016 Amphibians of Costa Rica: A field guide. Ítaca, Nueva York, Estados Unidos de América. Zona Tropical Publications. - Acosta-Chaves, Víctor José (2017)
Book review directed to local tourism guides, naturalists and biologists on the new book “Amphibians of Costa Rica: A field guide” by Twan Leenders.